Character, identity formation in North Borneo (Sabah), Malaysia: study and investigation into identities in terms of language use - Irfan Ullah; Mokhtar Saidin; Anderson, Bobby (Ikatan Ahli Arkeologi Malaysia, Universiti Kebangsaan Malaysia, 2018)
During the years after initial Malaysian independence in 1957, the North Borneo (Sabah) region became part of the Malaysian Federation, forming the provinces of Sabah and Sarawak. Unlike Peninsular Malaysia, though, Malaysian Borneo had a highly diverse indigenous and migrant population that far outweighed the population of Muslim Malays. Today, Malaysian Borneo still consists of a highly diverse population of indigenous peoples and migrants with a minority of people who identify as Malay. Over 85% of people in Sabah are non-Malay. This article pursues ethnographic and historical background of Malay and Bornean identities is discussed to set a foundation for the analysis of identity formulation in Sabah, Malaysia. Additionally, this includes a discussion of the theoretical frameworks that will be used for the analytic discussion of identity formulation. The methods I carried out, including library research and fieldwork, are discussed in the present the data collected from library research and fieldwork on identities in Sabah. The fieldwork demonstrated that Sabahans have embraced the Malay language and the type of Malay spoken in Sabah is unique to their region.